Perbandingan Kinerja Teknik Modulasi Inverter Dua-Level untuk Pengaturan Kecepatan Motor Induksi Tiga-Fase - I Nyoman Wahyu Satiawan; Ida Bagus Fery Citarsa; Supriono . (Jurnal Arus Elektro Indonesia, 2015)
AbstractThis paper compares various modulation techniques of twolevelinverter, i.e 180 conduction method, Sin-PWM (SPWM) andspace vector PWM (SVPWM). Simulation result shows that 180conduction mode is able to generate the highest voltage outputhowever it results the worse performance. Comparison offundamental component of the output voltage is 0.637 : 0.5 : 0.57p.u for 180 conduction method, SPWM and SVPWM respectively.Meanwhile comparison of voltage output THD is 31% : 68% : 30%and comparison of phase stator current THD is 50 % : 24% : 9.7%for 180 conduction method, SPWM and SVPWM respectively.Furthermore, relationship of speed - torque shows that when motoris fed by inverter using 180 conduction method, motor is able toreach the highest speed (1765 rpm) but results high torque ripplecompare to SVPWM (1685 rpm) and SPWM (1460 rpm). It is alsoshown that the SVPWM method performs the smoothest torqueripple among the three modulation methods. The results prove thatSVPWM method is the most suitable method for variable speeddrive of a three-phase induction motor.Keywords— 180 conduction method, SPWM method, SVPWM method, Total Harmonics Distortion (THD), Three-phase induction motor speed drive.